Giant Optical Activity in an All‐Dielectric Spiral Nanoflower. Issue 31 (3rd July 2018) - Xiao, Ting‐Hui; Cheng, Zhenzhou; Goda, Keisuke
Abstract: Optical activity is an effect of prominent importance in stereochemistry, analytical chemistry, metamaterials, spin photonics, and astrobiology, but is naturally minuscule. Metallic nanostructures are commonly exploited as basic elements for artificially producing large optical activity by virtue of surface plasmon resonance (SPR) on the nanostructures. However, their intrinsic high ohmic loss amplified by the SPR results in low energy efficiency and large photothermal heat generation, severely limiting their performance and practical utility. Giant optical activity by inducing magnetic resonance in an all‐dielectric spiral nanoflower (spiral‐flower‐shaped nanostructure) is demonstrated here. Specifically, a large circular‐intensity difference of ≈35% is theoretically predicted and experimentally demonstrated by optimizing the magnetic quadrupole contribution of the nanoflower to scattered light. The nanoflower overcomes the bottleneck of the traditional metallic platforms and enables the development of diverse chiroptical devices and applications. Abstract : Giant optical activity in an all‐dielectric spiral nanoflower is realized by manipulating optical magnetic resonance. A largest‐to‐date circular intensity difference of ≈35% is experimentally demonstrated. The all‐dielectric nanoflower overcomes the low energy efficiency and large photothermal heat generation in traditional metallic platforms and enables the development of diverse chiroptical devices and applications.